Biomarkers and immunotherapy in endometrial cancer: mechanisms and clinical applications - Zhao, Lianfang; Li, Xiaohong; Jing, Yaling; Tang, Liping; Lin, Fang; Zhang, Yongqiang; Tang, Yuqin; Chen, Chuanliang; Yang, Jiayan; Liu, Xiaofang; Chen, Jianhui (Frontiers in Immunology, 2025)
Advanced endometrial cancer (EC) poses significant therapeutic challenges due to molecular heterogeneity and immune evasion. Immune checkpoint inhibitors (ICIs) show promise, particularly in mismatch repair-deficient (MMRd) and POLE-mutated subtypes, but resistance remains a barrier. This review synthesizes recent advances in biomarker-driven immunotherapy for EC, focusing on predictive biomarkers (e.g., LRP2, FANCE, MSH2, miRNA signatures), combination strategies (ICIs with anti-angiogenics or PARP inhibitors), and challenges in clinical translation. We highlight the impact of tumor microenvironment components, emerging technologies like machine learning, and future directions for personalized immunotherapy. Standardizing biomarker testing and optimizing trial designs will be critical to overcome resistance and improve outcomes.